What Grasps and Holds 8-Month-Old Infants' Looking Attention? The Effects of Object Size and Depth Cues. (10th June 2012) - Guan, Yu; Corbetta, Daniela
Abstract : The current eye-tracking study explored the relative impact of object size and depth cues on 8-month-old infants' visual attention processes. A series of slides containing 3 objects of either different or same size were displayed on backgrounds with varying depth cues. The distribution of infants' first looks (a measure of initial attention switch) and infants' looking durations (a measure of sustained attention) at the objects were analyzed. Results revealed that the large objects captured infants' attention first, that is, most of the times infants directed their visual attention first to the largest object in the scene regardless of depth cues. For sustained attention, infants preferred maintaining their attention to the largest object also, but this occurred only when depth cues were present. These findings suggest that infants' initial attention response is driven mainly by object size, while infants' sustained attention is more the product of combined figure and background processing, where object sizes are perceived as a function of depth cues.